Seroprevalence of peste des petits ruminants in sheep and goats managed under pastoral and agro-pastoral systems - Mwanandota, Julius Joseph; Msuta, Gilbert; Mdetele, Daniel; Sallu, Raphael; Omondi, George Paul; Chengula, Augustino; Kimera, Sharadhuli; Parida, Satya; Misinzo, Gerald (The Journal of Infection in Developing Countries, 2024)
Introduction: Peste des petits ruminants (PPR) is an infectious disease that imposes substantial economic burdens on small ruminants (SR) production. For Tanzania to develop efficient management and eradication plans, it is essential to comprehend the seroprevalence of PPR designated for global elimination by 2030. Methodology: This study investigated the prevalence of PPR in animals kept under pastoral and agropastoral communities in Tanzania. A total of 1,128 blood samples from SR were collected and analyzed for PPR-specific antibodies using the HPPR-b ELISA technique. Multivariate logistic regression was used to analyze the risk factors Results: The overall seroprevalence was 10%. Higher seropositivity was observed in the Kiteto, Longido, and Simanjiro districts of the northern zone and the Mbarali district of the southern highlands, with the seroprevalence decreasing trend from the northern to southern zones. Multivariate logistic regression analysis for risk factors identified significant differences in seroprevalence across disease surveillance zones, with odds ratios (OR) ranging from 2 to 3. Conclusions: Agropastoral production systems exhibited lower PPR seroprevalence compared to pastoral systems. The increasing seropositivity in the Mbarali district suggests a southward spread of PPR, increasing a threat to Tanzania`s southern regions and neighboring countries. The disease`s dissemination is closely linked to livestock trading infrastructure, highlighting the need for periodic seromonitoring. Control efforts should prioritize highly affected northern zones and implement strict regulations on animal movement to protect less-affected southern areas.